2015
DOI: 10.1007/s11051-015-3081-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiation synthesized poly(n-vinyl-2-pyrrolidone)-stabilized-gold nanoparticles as LSPR-based optical sensor for mercury ions estimation

Abstract: Poly(n-vinyl-2-pyrrolidone)-stabilizedgold nanoparticles (PVP-Au-NPs) have been synthesized via a green-60 Co-Gamma radiolytic route and employed as a localized surface plasmon resonance (LSPR)-based optical sensor for estimation of trace quantities of Hg 2? ion in aqueous solutions. The in situ generated PVP-Au-NPs were characterized using UV-vis spectroscopy, transmission electron microscopy, and particle size analysis techniques. Reaction conditions were optimized to obtain uniformly dispersed PVP-Au-NPs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
2
1
Order By: Relevance
“…In this work, we obtained the sensitivity 0.28 nm/mM and limit of detection of 800μM (65 ppm) of Pb 2+ ions. In comparison to earlier reported limit of detection values of heavy metal ions, such as 0.36 μM for Pb 2+ [5], 0.1μM for Hg 2+ ions [6], 25μM Hg 2+ + 79μM Cu 2+ [13], our reported value is slightly higher. However, the real strength of our sensor lies in its reusability, portability, mechanical robustness, ease of fabrication and lowcost setup because it does not need expensive and bulky source, detector, collimator, lenses, fusion splicer, etc.…”
Section: G Performance Comparison With Prior Workcontrasting
confidence: 87%
See 1 more Smart Citation
“…In this work, we obtained the sensitivity 0.28 nm/mM and limit of detection of 800μM (65 ppm) of Pb 2+ ions. In comparison to earlier reported limit of detection values of heavy metal ions, such as 0.36 μM for Pb 2+ [5], 0.1μM for Hg 2+ ions [6], 25μM Hg 2+ + 79μM Cu 2+ [13], our reported value is slightly higher. However, the real strength of our sensor lies in its reusability, portability, mechanical robustness, ease of fabrication and lowcost setup because it does not need expensive and bulky source, detector, collimator, lenses, fusion splicer, etc.…”
Section: G Performance Comparison With Prior Workcontrasting
confidence: 87%
“…A number of nanoparticle-based heavy metal techniques have been reported in the last two decades and among the varieties of nanoparticles available, gold nanoparticles (Au NPs) offer unique advantages in terms of a high Refractive Index (RI)-sensitive Localized Surface Plasmon Resonance (LSPR) peak, coupled to resistance to oxidation, ease of fabrication and well-understood surface chemistry [4,5]. Mishra et al have, for example, incorporated poly-(n-vinyl-2-pyrrolidone) ((C6H9NO)n) as a capping agent to create a LSPR-based mercury ion sensor [6]. Similarly, Youngjin Kim et al have demonstrated a colorimetric sensor using the aggregation of 11-Mercaptoundecanoic acid (MUA; HS(CH2)10CO2H) functionalized Au NPs in presence of heavy metal ions [7].…”
Section: Introductionmentioning
confidence: 99%
“…16 These properties make them quite attractive to design colorimetric sensors 17 or to develop promising applications for biology and catalysis. 18,19 Recently, Au NPs synthesized in the presence of different capping agents such as DNA, 20 enzymes, 21 and conjugated polymers 22 have been applied to mercury detection. Chen et al described an effective strategy to fabricate a highly sensitive and selective DNAbiosensor for the determination of Hg 2þ with a very low detection limit (0.05 nM).…”
Section: Introductionmentioning
confidence: 99%